2020
DOI: 10.1002/lary.29301
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Extralaryngeal Spread in Juvenile Recurrent Respiratory Papillomatosis

Abstract: Objectives/Hypothesis: To identify factors associated to increased risk of extra-laryngeal spread in pediatric patients with recurrent respiratory papillomatosis (RRP).Study Design: Retrospective chart review.Methods: A retrospective study was conducted evaluating the clinical charts of patients younger than 16 years with histopathologically confirmed RRP treated between January 2014 and December 2018. Characteristics of patients with and without extra-laryngeal disease dissemination were compared. Odds ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Various hypotheses have been proposed to explain this distal spread, including the extension of papillomas by contiguity, diffuse viral contamination, and iatrogenic factors, such as laryngoscopy, bronchoscopy, tracheostomy, and surgical manipulation. Risk factors for the spread of RRP toward the lower respiratory tract include HPV11 infection, age younger than 5 years, tracheostomy performed to avoid airway obstruction, and previous invasive procedures [ 80 , 81 ]. Gélinas et al (2008) reviewed cohort studies on RRP, and 3.3% (55/1666) of the patients) had pulmonary involvement [ 82 ].…”
Section: Laryngeal Squamous Cell Papillomas (Rrp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Various hypotheses have been proposed to explain this distal spread, including the extension of papillomas by contiguity, diffuse viral contamination, and iatrogenic factors, such as laryngoscopy, bronchoscopy, tracheostomy, and surgical manipulation. Risk factors for the spread of RRP toward the lower respiratory tract include HPV11 infection, age younger than 5 years, tracheostomy performed to avoid airway obstruction, and previous invasive procedures [ 80 , 81 ]. Gélinas et al (2008) reviewed cohort studies on RRP, and 3.3% (55/1666) of the patients) had pulmonary involvement [ 82 ].…”
Section: Laryngeal Squamous Cell Papillomas (Rrp)mentioning
confidence: 99%
“…Tracheal papilloma (TP) is a distinct rarity, mostly manifested as the tracheal involvement of RRP. TPs have both a juvenile and an adult onset, presenting with either a JO- or AO-papillomatosis, mostly due to the distal spread of RRP from the larynx [ 80 , 81 , 82 ]. TPs are more common (3–26%) than pulmonary involvement (1–3%).…”
Section: Tracheal Papillomas (Tp)mentioning
confidence: 99%
“…Previous research found that endotracheal intubation aggravated distal spread, and the longer the tube carrying time, the longer the disease time, affecting the remission rate and mortality of patients [12,13] . A study in Argentina of 82 patients with RRP under 16 years of age comparing the characteristics of RRP patients with or without extralaryngeal spread found that age younger than 5 years or history of tracheostomy at the time of diagnosis of RRP were factors associated with extralaryngeal spread, and the occurrence of extralaryngeal spread was also associated with HPV subtype 11 infection [14] .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The factors that act as triggers for the growth of laryngeal papillomas are still unknown, and the risk factors for the aggressive form of the disease have not yet been fully elucidated. 2,3,7,[13][14][15][16][17][18][19] Laryngopharyngeal reflux (LPR) has been proposed both as a trigger for RRP onset and as an exacerbating factor leading to disease recurrence. 12,[20][21][22][23][24] Reflux of gastric contents to the level of the larynx causes significant damage to the mucosa and has been implicated in various laryngeal pathologic lesions.…”
Section: Introductionmentioning
confidence: 99%